Introducing Automated Verification and Validation for Virtualized Network Functions and Services - Peuster, Manuel; Schneider, Stefan Balthasar; Zhao, Mengxuan; Xilouris, George; Trakadas, Panagiotis; Vicens, Felipe; Tavernier, Wouter; Soenen, Thomas; Vilalta, Ricard; Andreou, George; Kyriazis, Dimosthenis; Karl, Holger (IEEE Communications Magazine)

A high dynamic range optical detector for measuring single photons and bright light - Tiedau, Johannes; Meyer-Scott, Evan; Nitsche, Thomas; Barkhofen, Sonja; Bartley, Tim; Silberhorn, Christine (Optics Express)

Can stimuli improve business model idea generation? Developing software-based tools for business model innovation - Szopinski, Daniel (Proceedings of the ACM Creativity & Cognition)
A business model describes the mechanisms whereby a firm creates, delivers, and captures value. Following the steadily growing interest in business model innovation, software tools have shown great potential in supporting business model development and innovation. Yet, understanding the cognitive processes involved in the generation of business model ideas is an aspect of software design-knowledge that has so far been neglected. To investigate whether providing stimuli – in this case, brainstorming questions – can enhance individual creativity in this context, we conduct an exploratory experiment with over 100 participants. Our study is the first to systematically investigate the process of idea generation using a software-based business model development tool with stimuli. Our preliminary findings have the potential to support the future development of business model development tools and to refine the research design used to evaluate such tools.
Keywords: Business model innovation; idea generation; cognitive stimuli; business model development tools; experiment; creativity support system

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning

Strong nonlinear optical response from ZnO by coupled and lattice-matched nanoantennas - Protte, Maximilian; Weber, Nils; Golla, Christian; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Secular stagnation? Is there statistical evidence of an unprecedented, systematic decline in growth? - Fritz, Marlon; Gries, Thomas; Feng, Yuanhua (Economics Letters)

On-the-fly Usability Evaluation of Mobile Adaptive UIs through Instant User Feedback - Yigitbas, Enes; Jovanovikj, Ivan; Josifovska, Klementina; Sauer, Stefan; Engels, Gregor (Proceedings of the 17th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT 2019))

Crowd-Driven Competitive Intelligence: Understanding the Relationship between Local Market Competition and Online Rating Distributions - Gutt, Dominik; Herrmann, Philipp; Rahman, Mohammad (Information Systems Research)

Can Experience be Trusted? Investigating the Effect of Experience on Decision Biases in Crowdworking Platforms - Görzen, Thomas (Proceedings of the 52nd Hawaii International Conference on System Sciences (HICSS))

Wertgenerierung bei M&A Transaktionen durch Bekanntgabe von Synergien? - Mehring, Oliver; Sievers, Sönke; Keienburg, Georg; Kengelbach, Jens
Öffentlich gelistete Firmen, die die Mehrheit an anderen börsennotierten Unternehmen er-werben und den Kapitalmarkt an den Synergieerwartungen teilhaben lassen, werden mit höheren kumulativen abnormalen Renditen im Ankündigungszeitpunkt belohnt verglichen mit solchen Unternehmen, die diese geheim halten. Des Weiteren ist die empirische Evi-denz konsistent mit der Idee, dass diese Käuferunternehmen ihre Transaktionen besser in-tegrieren, weil auch die industrieadjustierten Ein- und Zweijahresrenditen der ankündigen-den Unternehmen ökonomisch und statistisch signifikant höher sind als die der zurückhal-tenden Käuferfirmen.

Multi-unit Bilateral Trade - Lazos, Philip; Goldberg, Paul; Skopalik, Alexander; Gerstgrasser, Matthias; de Keijzer, Bart (Proceedings of the Thirty-Third AAAI Conference on Artificial Intelligence (AAAI))
We characterise the set of dominant strategy incentive compatible (DSIC), strongly budget balanced (SBB), and ex-post individually rational (IR) mechanisms for the multi-unit bilateral trade setting. In such a setting there is a single buyer and a single seller who holds a finite number k of identical items. The mechanism has to decide how many units of the item are transferred from the seller to the buyer and how much money is transferred from the buyer to the seller. We consider two classes of valuation functions for the buyer and seller: Valuations that are increasing in the number of units in possession, and the more specific class of valuations that are increasing and submodular. Furthermore, we present some approximation results about the performance of certain such mechanisms, in terms of social welfare: For increasing submodular valuation functions, we show the existence of a deterministic 2-approximation mechanism and a randomised e/(1-e) approximation mechanism, matching the best known bounds for the single-item setting.

Using High Performance Computing for Unrelated Parallel Machine Scheduling with Sequence-Dependent Setup Times: Development and Computational Evaluation of a Parallel Branch-and-Price Algorithm - Rauchecker, Gerhard; Schryen, Guido (Computers & Operations Research)
Scheduling problems are essential for decision making in many academic disciplines, including operations management, computer science, and information systems. Since many scheduling problems are NP-hard in the strong sense, there is only limited research on exact algorithms and how their efficiency scales when implemented on parallel computing architectures. We address this gap by (1) adapting an exact branch-and-price algorithm to a parallel machine scheduling problem on unrelated machines with sequence- and machine-dependent setup times, (2) parallelizing the adapted algorithm by implementing a distributed-memory parallelization with a master/worker approach, and (3) conducting extensive computational experiments using up to 960 MPI processes on a modern high performance computing cluster. With our experiments, we show that the efficiency of our parallelization approach can lead to superlinear speedup but can vary substantially between instances. We further show that the wall time of serial execution can be substantially reduced through our parallelization, in some cases from 94 hours to less than six minutes when our algorithm is executed on 960 processes.
Keywords: parallel machine scheduling with setup times; parallel branch-and-price algorithm; high performance computing; master/worker parallelization

Walking the Middle Path: How Medium Trade-off Exposure Leads to Higher Consumer Satisfaction in Recommender Agents - Schuhbeck, Veronika; Siegfried, Nils; Dorner, Verena; Benlian, Alexander; Scholz, Michael; Schryen, Guido (Proceedings of the 14. Internationale Tagung Wirtschaftsinformatik)
Recommender Agents (RAs) facilitate consumers’ online purchase decisions for complex, multi-attribute products. As not all combinations of attribute levels can be obtained, users are forced into trade-offs. The exposure of trade-offs in a RA has been found to affect consumers’ perceptions. However, little is known about how different preference elicitation methods in RAs affect consumers by varying degrees of trade-off exposure. We propose a research model that investigates how different levels of trade-off exposure cognitively and affectively influence consumers’ satisfaction with RAs. We operationalize these levels in three different RA types and test our hypotheses in a laboratory experiment with 116 participants. Our results indicate that with increasing tradeoff exposure, perceived enjoyment and perceived control follow an inverted Ushaped relationship. Hence, RAs using preference elicitation methods with medium trade-off exposure yield highest consumer satisfaction. This contributes to the understanding of trade-offs in RAs and provides valuable implications to e-commerce practitioners.
Keywords: Recommender Agents; Preference Elicitation Method; Trade-off Exposure; Customer Satisfaction

Growth Trends and Systematic Patterns of Boom and Busts –Testing 200 Years of Business Cycle Dynamics - Gries, Thomas; Fritz, Marlon; Yuanhua, Feng (Oxford Bulletin of Economics and Statistics)

Heart over Heels? An Empirical Analysis of the Relationship between Emotions and Review Helpfulness for Experience and Credence Goods - Müller, Michelle; Gutt, Dominik (Wirtschaftsinformatik Proceedings 2019)

A Semi-Automated Approach for Generating Online Review Templates, - Poniatowski, Martin; Neumann, Jürgen; Görzen, Thomas; Kundisch, Dennis (Wirtschaftsinformatik Proceedings 2019)

Power Allocation with a Wireless Multi-cast Aware Routing for Virtual Network Embedding - Afifi, Haitham; Karl, Holger (2019 16th IEEE Annual Consumer Communications & Networking Conference (CCNC2019))

Always be Two Steps Ahead of Your Enemy - Maintaining a Routable Overlay under Massive Churn with an Almost Up-to-date Adversary - Götte, Thorsten; Vijayalakshmi, Vipin Ravindran; Scheideler, Christian (Proceedings of the 2019 IEEE 33rd International Parallel and Distributed Processing Symposium (IPDPS '19))
We investigate the maintenance of overlay networks under massive churn, i.e. nodes joining and leaving the network. We assume an adversary that may churn a constant fraction $α n$ of nodes over the course of $\mathcal{O}(\log n)$ rounds. In particular, the adversary has an almost up-to-date information of the network topology as it can observe an only slightly outdated topology that is at least $2$ rounds old. Other than that, we only have the provably minimal restriction that new nodes can only join the network via nodes that have taken part in the network for at least one round. Our contributions are as follows: First, we show that it is impossible to maintain a connected topology if adversary has up-to-date information about the nodes' connections. Further, we show that our restriction concerning the join is also necessary. As our main result present an algorithm that constructs a new overlay- completely independent of all previous overlays - every $2$ rounds. Furthermore, each node sends and receives only $\mathcal{O}(\log^3 n)$ messages each round. As part of our solution we propose the Linearized DeBruijn Swarm (LDS), a highly churn resistant overlay, which will be maintained by the algorithm. However, our approaches can be transferred to a variety of classical P2P Topologies where nodes are mapped into the $[0,1)$-interval.

Continuous relaxations for the traveling salesman problem - Sahai, Tuhin; Ziessler, Adrian; Klus, Stefan; Dellnitz, Michael (Nonlinear Dynamics)

Investigation on Inductive Heating of Sheet Metal for an Industrial Hot Stamping Process - Pfeifer, Florian; Dietrich, André; Marten, Thorsten; Tröster, Thomas; Nacke, Bernard (Proceedings of 7th International Conference on Hot Sheet Metal Forming of High-Performance Steel)